2006
DOI: 10.1111/j.1365-2036.2006.02768.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: safe amounts of gluten for patients with wheat allergy or coeliac disease

Abstract: SUMMARYFor both wheat allergy and coeliac disease the dietary avoidance of wheat and other gluten-containing cereals is the only effective treatment. Estimation of the maximum tolerated amount of gluten for susceptible individuals would support effective management of their disease.Literature was reviewed to evaluate whether an upper limit for gluten content in food, which would be safe for sufferers from both diseases, could be identified. When setting gluten limits for coeliac disease sufferers, the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
157
1
27

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(186 citation statements)
references
References 144 publications
(181 reference statements)
1
157
1
27
Order By: Relevance
“…Therefore, foods that contain wheat starch should be labeled as "low-gluten" (Fasano and Catassi, 2001). The proposed standard as formulated by the WHO/FAO organization Codex Alimentarius, has one limit at 0.02% for "rendered gluten-free" food, and another at 0.002% for "naturally gluten-free food" (Bai et al, 2013;Hischenhuber et al, 2005;Niewinski, 2008). These different practices reflect the fact that we do not know the exact limit of gluten intake that is tolerated long term without harmful effects by patients with celiac disease as a group (Ciclitira et al, 2005a).…”
Section: Gliadins and The Celiac Diseasementioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, foods that contain wheat starch should be labeled as "low-gluten" (Fasano and Catassi, 2001). The proposed standard as formulated by the WHO/FAO organization Codex Alimentarius, has one limit at 0.02% for "rendered gluten-free" food, and another at 0.002% for "naturally gluten-free food" (Bai et al, 2013;Hischenhuber et al, 2005;Niewinski, 2008). These different practices reflect the fact that we do not know the exact limit of gluten intake that is tolerated long term without harmful effects by patients with celiac disease as a group (Ciclitira et al, 2005a).…”
Section: Gliadins and The Celiac Diseasementioning
confidence: 96%
“…These different practices reflect the fact that we do not know the exact limit of gluten intake that is tolerated long term without harmful effects by patients with celiac disease as a group (Ciclitira et al, 2005a). The acceptable gluten dose per day is still under debate, although the scientific and medical communities have suggested that around 50 mg/day is safe (Hischenhuber et al, 2005). As a reference, the normal gluten intake by healthy individuals is about 13 g/day (Van Overbeek et al, 1997).…”
Section: Gliadins and The Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The European Union, World Health Organization, and Codex Alimentarius require reliable measurement of the wheat prolamins, gliadins, rather than all wheat-derived proteins [84]. There is still no general agreement on the analytical method to measure gluten in ingredients and food products [85], although the official limits described in the Codex Draft Revise Standard (2000) are 20 ppm for foodstuffs naturally gluten-free and Never-theless, to measure gluten traces in food, immunochemical methods are usually chosen to determine gliadins [87][88][89][90][91][92]. Besides the quality control of gluten-containing products, it is important to assess gluten in foodstuff that can be contaminated with native or heated proteins from wheat, barley, and rye.…”
Section: Gluten-free Food Controlmentioning
confidence: 99%
“…The modified peptides are able to bind to class II human histocompatibility leucocyte antigen (HLA) molecules DQ2 and DQ8. This recognition event appears to orchestrate an abnormal cellular-mediated immune response which triggers an inflammatory reaction which results in the flattened mucosa characteristic of Coeliac's disease (Hischenhuber et al, 2006).…”
Section: Introductionmentioning
confidence: 99%